178k views
3 votes
Is my solution correct?

Is my solution correct?-example-1
User Matt Sach
by
5.9k points

2 Answers

3 votes

Hello

3 (2-x)=7-4x

6-3x=7-4x

6-7=-4x+3x

-1=-x

x=1

Good Luck

Goodbye ♥

User Ravikiran
by
6.0k points
1 vote

Hello there!

Yes, your solution is correct! A way to check it is replacing the value you found for x into x in the equation.

3(2-x) = 7 - 4x ⇒ 3(2-1) = 7 - 4(1)

And now solve 3(2-1) = 7 - 4(1).

3(1) = 7 - 4(1)

3 = 7 - 4

3 = 3

Since it is a true statement that 3 is equal to 3, it means your solution of x = 1 is correct. Good job! :)

User Dube
by
6.0k points